Enhancement of Oral Bioavailability of Rosuvastatin Using Combinational Approach of Thermal Fraction of Clarified Butter - Sarwa, Dr. Khomendra Kumar (Asian Journal of Pharmaceutics (AJP), 2021)
Background: Thermal fractionation is an effective technique similar to chromatographic separation. Clarified butter (CB) is a mixture of fatty acid which shown different physiochemical properties if fractionated by various means. The present investigation was a study of the suitability of 30°C and 50°C thermal fractions of CB in various ratios for improvement of absorption of poorly aqueous soluble drug rosuvastatin (RSC). This work also tries to address the difficulty in in vitro dissolution data correlation with in vivo absorption characteristics in a practical situation. Aim: The author aims to get the best combination of 30°C and 50°C fractions which give desirable drug release with effective permeation. Materials and Methods: The 32 factorial design approach was used to formulate rosuvastatin CB complex using thermal fractions in various ratios. Drug CB complex was evaluated in various parameters such as contact angle, partition coefficient, saturation solubility, dissolution, and permeation characteristics. The change in physical and chemical properties of drug complex prepared with various ratios of the thermal fraction was also studied by X-ray diffraction and Liquid Chromatography-Mass Spectroscopy. Results and Discussion: The weight ratio of thermal fraction of CB (TFCB) fractionated at 30°C and TFCB fractionated at 50°C in 1:1.5 w/w in formulation RAE-B2 was found suitable to improve the absorption characteristics of rosuvastatin. The ex vivo permeation studies showed 90.68% permeation of rosuvastatin from RAE-B2 formulation which was found to higher than other formulation as well as pure rosuvastatin. Conclusion: The result suggested that the drug complex prepared using 30°C and 50°C fractions at 1:1.5 shown optimum drug release with desired permeation.